Conceptualizing the North - Lilli Mittner; Kate Maxwell; Hanne Hammer Stien (Nordlit: Tidsskrift i litteratur og kultur, 2020)
In this article that opens and introduces the special issue Conceptualizing the North, we present our theoretical rationale behind the conceptualization(s) of the north presented both in our article and in the issue as a whole, as well as our approach to the co-creative peer review. Through new material feminist understanding of the north, we acknowledge our kin both past and present, and unfold a spectrum of possible understandings by looking at, reading through, hearing, experiencing, and sensing the north. Ultimately, the issue unites, rather than divides, scholarly and artistic approaches that simultaneously conceptualize and analyse the north.